2015
DOI: 10.1111/j.1564-913x.2015.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of employment in Latin America: Theory and evidence

Abstract: Artículo de publicación ISISin acceso a texto completoHistorically, the development literature concerned with Latin American labour markets has focused on job numbers and productivity. But given the persistence of large shares of informal and now otherwise precarious employment, the authors argue that meaningful analysis also requires consideration of the implications of occupational status for the quality of employment. Based on empirical evidence from recent decades, they conclude that most dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…These results may seem counterintuitive but make sense if we take into account that self-employed workers rarely become unemployed as they have no employer to make them redundant. In general, self-employed workers in Latin America have more stable jobs than salaried workers, although their income levels may fluctuate significantly during economic downturns (Ramos et al, 2015).…”
Section: Deprivation Rates By Indicatormentioning
confidence: 99%
“…These results may seem counterintuitive but make sense if we take into account that self-employed workers rarely become unemployed as they have no employer to make them redundant. In general, self-employed workers in Latin America have more stable jobs than salaried workers, although their income levels may fluctuate significantly during economic downturns (Ramos et al, 2015).…”
Section: Deprivation Rates By Indicatormentioning
confidence: 99%
“…11 Some policies sought deregulation of the labour market, leading to a greater flexibilisation of working hours, generation of contracts with limited duration, incentives for outsourcing, and cost reduction in dismissal. 12 (p180)…”
Section: Neoliberalism and Its Effects On The Labour Marketmentioning
confidence: 99%
“…Various studies have concluded that the period 1950-1970 witnessed major transformations in the composition of the labor force as non-manual occupations in the secondary and tertiary sectors expanded and significant upward social mobility ensued. 10 The post-World War II industrialization had generated productive employment and, most significantly, brought a working class onto the stage and created the conditions for a dynamic labor movement.…”
Section: The National Developmental Statementioning
confidence: 99%
“…In Uruguay, by contrast, the various left governments "had built up the unions' organizational resources while doing little to limit their power, and they have done so in spite of employer opposition. " 34 This led a renewed role for collective bargaining between labor and capital, with only a limited role for the state. Brazil stood somewhere in between, with some more restricted elements, while the role of the trade unions in forming the governing Workers' Party gave it a certain degree of leverage.…”
Section: The Left Decadementioning
confidence: 99%